(untitled) (The Pakistan Development Review, 2007)
Multinational enterprises (MNEs) not only generate global flows of foreign direct investment, but are also extremely for global trade flows. UNCTAD (2004) estimates that MNEs account for around two-thirds of world exports. Since MNEs are responsible for a large proportion of world trade, one may infer that there is a close relationship between flows of FDI and trade. An MNE network, consisting of a parent and a network of affiliates, generates simultaneous flows of goods and investments. In this context the pool of knowledge and associated models, which explain international trade, has grown substantially in the recent past, but there is less theoretical consensus about the relationship between trade flows and FDI. The fact that exporting and local production are alternative ways for an MNE to serve the demand in a foreign market suggests a substitutability relationship between FDI and trade. MNE production in the host country implies that local production is a substitute for exports from the home country. On the other hand, MNE affiliates’ production in a host country can generate a demand for intermediate goods from the parent, resulting in a complementary relationship between flows of FDI and trade (exports). Theoretical reasoning therefore supports both these possibilities, providing a strong incentive for empirical analysis